Answer :
Use the quadratic equation to solve this (image of the quadratic equation is below)
Remember that quadratic functions are set up like so:
[tex]ax^{2} +bx +c = 0[/tex]
To make the equation 3x² + 4x = -8 into a quadratic function you must bring -8 to the left side of the equation so it equals zero. To do this add 8 to both sides
3x² + 4x + 8= -8 + 8
3x² + 4x + 8 = 0
That means that in this equation...
a = 3
b = 4
c = 8
^^^Plug these numbers into the quadratic equation and solve (Keep in mind that +/- is ± )
[tex]\frac{-4+/-\sqrt{(4)^{2}-4(3)(8)}}{2(3)}[/tex]
[tex]\frac{-4+/-\sqrt{16-96}}{6}[/tex]
[tex]\frac{-4+/-\sqrt{-80}}{6}[/tex]
^^^There is no real solution to this equation. You must have an imaginary solution
[tex]\frac{-4+/-i\sqrt{80}}{6}[/tex]
Simplify
[tex]\frac{-2+/-2i \sqrt{5}}{3}[/tex]
Hope this helped!
~Just a girl in love with Shawn Mendes
